The effect of flexibility on athlete's passing ability at football school nuansa fc u 14-17 at padang city - Hendro Wardoyo; Diah Primi; ayu purnama wenly (Program Pascasarjana Universitas Negeri Jakarta, 2022)
This type of research is quantitative research with a simple correlation approach. The purpose of study is to determine the effect of flexibility on athlete's passing ability at football school nuansa fc u 14-17 at Padang city. The population is athletes at Nuansa FC U 14-17 Football School, Padang city, totaling 25 people. The sampling technique used is saturated sampling. So that, in this study the samples are all athletes at Nuansa FC U 14-17 Football School in Padang City. The instrument for measuring athlete flexibility uses the sit and reach flexibility test. Then, the passing test uses the short pass test. The data collection technique that will be used is by administering instruments in the form of tests to the Nuansa FC U 14-17 Football School players who are the samples in the study. Data were analyzed with product moment correlation using SPSS application 26. Based on the results of data analysis, the results show that sig. (2-tailed) 0.000 < α 0.05, then correlate. The effect of flexibility on the passing ability of Nuansa FC U 14 - 17 Football School in Padang City is 0.863. based on the guidelines for the degree of relationship, the Pearson correlation value is 0.863 = perfect correlation. Thus, it can be concluded that there is a significant relationship between flexibility and the passing ability of Nuansa FC U 14-17 Football School players in Padang City.